2017
DOI: 10.1164/rccm.201609-1846oc
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal Type 2 Innate Lymphoid Cells Are a Key Component of the Allergic Response to Aeroallergens

Abstract: The rapid recruitment of ILC2s to the upper airways of allergic patients with rhinitis, and their association with key type 2 mediators, highlights their likely important role in the early allergic response to aeroallergens in the airways. The novel methodology described herein enables the analysis of rare cell populations from noninvasive serial tissue sampling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 40 publications
2
70
0
1
Order By: Relevance
“…Further, an in vitro study has demonstrated allergen extract‐induced IL‐5 release from peripheral blood mononuclear cells from asthmatics, which should incorporate both ILC2s and Th2 cells, independent of atopy . Interestingly, the recruitment of ILC2 cells after nasal allergen exposure was found to be related to total serum IgE, but not atopy, in a recent study …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Further, an in vitro study has demonstrated allergen extract‐induced IL‐5 release from peripheral blood mononuclear cells from asthmatics, which should incorporate both ILC2s and Th2 cells, independent of atopy . Interestingly, the recruitment of ILC2 cells after nasal allergen exposure was found to be related to total serum IgE, but not atopy, in a recent study …”
Section: Discussionmentioning
confidence: 95%
“…IgE formation may be promoted primarily by T helper cell type 2 (Th2 cells), and this formation increases with allergen exposure. However, ILC2s may also be activated by allergen exposure …”
Section: Introductionmentioning
confidence: 99%
“…The biologically relevant non-T cell source of IL-5, as confirmed by IL-5 reporter mice 69 , is group 2 innate lymphoid cells (ILC2s), which are major IL-5-expressing cells within tissues 69,74 . ILC2-derived IL-5 is implicated in the homeostatic homing of eosinophils into the small intestine 69 , eosinophil-dependent metabolic homeostasis in tissues 75 and fostering an eosinophil-rich inflammatory exudate into the lungs during an allergic response 76 (including in humans 77,78 ). The epithelial cell-derived alarmins, IL-25, IL-33 and thymic stromal lymphopoietin, promote eosinophilia in part by eliciting IL-5 production by ILC2s 79,80 .…”
Section: Regulating Tissue Eosinophilsmentioning
confidence: 99%
“…22 Moreover, ILC2 numbers are elevated in the blood after intranasal allergen challenge of cat-sensitized adults 23 and during the grass pollen season in grass allergic patients as well as in the nasal fluid upon grass pollen challenge. 24 However, allergen-dependent differences have been reported. receptor, IL-13, and the transcription factor RORa, which are all essential for ILC2s, 37 and by (ii) the finding of increased expression of IL-25, IL-33, and TSLP in lungs and sputum of asthma patients.…”
Section: Ilc3smentioning
confidence: 99%